The Application of Enterpreneurship Program at Packet C PKBM Assolahiyah - Heru Saleh; Aldian Hudaya (IKIP Siliwangi Bandung, 2019)
This research aims to describe the application of an entrepreneurship program to a community of packet C learners situated at PKBM Assolahiyah: the process, the results, the influencing factors, and the impacts toward the learning community. The subjects of this research include the program organizer, the tutors, and the learning community themselves. The data gathering methods include observation, interview, and study of documents. The data analysis method consists of three steps: data reduction, data display, and conclusion drawing. This research concludes that the 5 steps program enables its learning community to develop and display skills of entrepreneurship. The supporting factors include the availability of monetary equity, organizer support, strong motivation from the learning community and overall community support. The hindering factors include land availability limitations, community limitations, and constant funding availability issues. This program has economic impacts (enabling the community to start their own business, an increase of their household incomes, and the fulfillment of household needs), psychological impacts (the development of self-confidence and hard-working attitude in the community) and social impacts (encouraging the community to participate actively in community organizations, extending the community members’ networks, and an ability to share their knowledge to the others).